Should parents be asked to consent for life-saving paediatric interventions?. (November 2021) - Gamble, Nathan K.; Pruski, Michal
Informed consent, when given by proxy, has limitations: chiefly, it must be made in the interest of the patient. Here we critique the standard approach to parental consent, as present in Canada and the UK. Parents are often asked for consent, but are not given the authority to refuse medically beneficial treatment in many situations. This prompts the question of whether it is possible for someone to consent if they cannot refuse. We present two alternative and philosophically more consistent frameworks for paediatric proxy consent. The first allows meaningful consent (parents may say 'yes' or 'no' to treatment), provided that parents are medically informed/competent and intend the health and well-being of their child. In the second solution, medical practitioners or the state consent for treatment, with parents only being consulted to help give insight to the child's circumstances. While we contend that either of these two options is superior to the insincerity of the present paradigm, we suggest that the first solution is preferable.